2014
DOI: 10.4082/kjfm.2014.35.5.227
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Hemorrhoids in Korean Adults: Korean National Health and Nutrition Examination Survey

Abstract: BackgroundAlthough hemorrhoids are one of the most common anal diseases among Koreans, risk factors for hemorrhoids have not been well identified.MethodsWe analyzed the data from the 4th Korean National Health and Nutrition Examination Survey (KNHANES) between 2007 and 2009. Study subjects were 17,228 participants of KNHANES who were aged 19 years or older. Logistic regression analysis was conducted to evaluate associations between hemorrhoids and probable risk factors.ResultsOverall prevalence of hemorrhoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 23 publications
4
70
3
4
Order By: Relevance
“…In addition, frequent recurrence, incomplete elimination of discomfort even after hemorrhoidectomy and postoperative discomfort including pain, made haemorrhoids the biggest problem all over the world that hinders patient's ability to live normally and work efficiently. 1 It is difficult to know the exact prevalence of haemorrhoids due to the embarrassing nature of the disease. Some researchers suggest that about 75 % of people will have symptomatic haemorrhoids at some point of time in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, frequent recurrence, incomplete elimination of discomfort even after hemorrhoidectomy and postoperative discomfort including pain, made haemorrhoids the biggest problem all over the world that hinders patient's ability to live normally and work efficiently. 1 It is difficult to know the exact prevalence of haemorrhoids due to the embarrassing nature of the disease. Some researchers suggest that about 75 % of people will have symptomatic haemorrhoids at some point of time in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Survey study proves that hemorrhoids is independently associated with depression in both men and women 13 . It is well known that our psychological status is directly associated with the digestion of food.…”
Section: Psychological Factorsmentioning
confidence: 73%
“…Approximately 25% of British people and 75% of American citizens, especially pregnant women and elderly adults, experience haemorrhoids at some point in their lives (Tucker, George, Barnett, & Longson, ). Other reports have shown that haemorrhoids in adults are 14.4% and 38.9% prevalent in South Korea and Australia, respectively (Lee, Kim, Kang, Shin, & Song, ; Riss et al., ). In 2015, a large‐scale epidemiological investigation demonstrated that the prevalence rate of haemorrhoids in urban and rural permanent residents aged over 18 years in China was as high as 50.28% (Jiang, Zhang, Sui, Li, & Yan, ).…”
Section: Introductionmentioning
confidence: 92%
“…Approximately 25% of British people and 75% of American citizens, especially pregnant women and elderly adults, experience haemorrhoids at some point in their lives (Tucker, George, Barnett, & Longson, 2008). Other reports have shown that haemorrhoids in adults are 14.4% and 38.9% prevalent in South Korea and Australia, respectively (Lee, Kim, Kang, Shin, & Song, 2014;Riss et al, 2012).…”
Section: Prevalence Of Haemorrhoidsmentioning
confidence: 99%